Building climate resilience in health systems: a climate vulnerability and capacity assessment in a rural hospital in Chad - Schwerdtle, Patricia; Zidouemba, Didier Tokoumnogo; Dermbaye, Alexi Reouhiri; Jobanputra, Kiran; Mcrae, Melissa; Tarabbo, Melanie; Njouonkou, Mohamed; Madjissem, Marius; Robert, Alexandre; Haider, Zia (Annals of global health, 2025)
Background: Chad is highly vulnerable to climate change, posing significant threats to health systems and population health. Rising temperatures, irregular rainfall, droughts, and resource scarcity exacerbate food insecurity, malnutrition, and vector-borne diseases like malaria. In Ngouri, a rural area in the Lac Region, these climate stressors have led to worsening health outcomes and strained healthcare services. Without adaptation measures, facilities will struggle to maintain essential services amid escalating climate pressures. This case study presents a facility-adapted climate vulnerability and capacity assessment (VCA) for a rural hospital in Chad, identifying key risks and prioritizing solutions to enhance climate resilience. Objectives: This case study describes the development and implementation of a facility-adapted climate VCA in a high-vulnerability, low-resource setting and outlines prioritized solutions for an actionable adaptation plan. Methods: The study employed a participatory mixed-methods design, incorporating five stages: (1) literature review on climate hazards, exposure pathways, and population vulnerabilities; (2) facility audit assessing infrastructure and healthcare delivery gaps; (3) qualitative focus groups to refine risk identification; (4) development of a matrix of solutions with cost estimates and feasibility analysis; and (5) a participatory prioritization process to develop a multi-year facility improvement plan. Findings: The VCA identified climate risks, including elevated malarial mortality and power outages disrupting oxygen supply. A list of 35 solutions was generated, with 22 priority actions selected for implementation. These included anticipatory planning, community sensitization, supplementary feeding programs, and improved waste management. The process highlighted the importance of community engagement, multidisciplinary collaboration, and staff motivation for climate-resilient and sustainable healthcare. Conclusion: The adapted VCA offers a replicable approach to assessing climate-related vulnerabilities and capacities in healthcare facilities. It revealed significant risks to health service delivery and informed the development of locally feasible, sustainable adaptation measures. The framework applied in Ngouri hospital demonstrates relevance for similarly affected contexts, supporting efforts to align health systems with global sustainability goals and to secure quality healthcare under changing climatic conditions.
Online veröffentlicht: 19. August 2025
Gesehen am 12.01.2026